Thermodynamic functions of activation for viscous flow for solutions of polyethylene glycol methyl derivatives with n-alcohols at different temperatures - Ferreyra de Ruiz Holgado, Mercedes Marta Elsa (2000)
Viscosity of dilute solutions of mono and dimethyl ether of polyethylene glycol in n-propanol and n-butanol has been determined at different temperatures, between 278.15 and 318.15 K. Thermodynamic functions of activation for viscous flow (Gibbs free energy, enthalpy and entropy) and also partial molar properties were obtained and analyzed using Eyring's theory of rate process applied to viscous flow. From the relation between thermodynamic functions of activation with the mole fraction of the solute, empirical coefficients have been calculated. Contributions to Jones-Dole coefficient, B, were analyzed.